Pendampingan Penerapan Pembelajaran Moderasi Beragama Bagi Guru Pendidikan Agama Islam di Madrasah - Ainul Yaqin; M. Syarif; Syaikhu Rozi (TAAWUN, 2023)
This service program aims to assist teachers to have the ability to detect the religious views and attitudes of students and to implement religious moderation learning in class. The steps for implementing the program include a) Introduction by conducting a needs analysis for the implementation of assistance; b) Implementation of the program by strengthening the teacher's ability to detect students' religious moderation issues and implementing religious moderation learning in class. Program implementation activities are carried out by means of intensive discussions in group discussion forums (FGD), delivery of workshop materials, and assistance in the implementation of religious moderation learning; the last activity is c) assessment and writing of service results reports. The service program with these steps has proven to be successful in achieving the planned goals. This is shown by the following indicators: 1) The teacher shows quite high enthusiasm in the discussions at the FGD forum; 2) The teacher's knowledge and ability to detect students' religious moderation issues, as well as the implementation of religious moderation learning, has proven to increase when compared between before the implementation of the service program and after the program implementation.